Computerized spatial language generation for object location. Issue 3 (September 2016) - Lara, Graciela; Antonio, Angélica; Peña, Adriana
Abstract Spatial language is the syntax used for object or place locations. Because an object location is inherently relative, it implies a frame of reference, which in turn may be aided by a reference object, other than the one to be located. This reference object is commonly selected based on its perceptual salience, that is, its more prominent features. Computer systems linked to various research areas have been developed to facilitate the communication and/or interpretation of spatial language for localization tasks. In this paper is presented a literature review of computer systems that adopt spatial language and perceptual salience for object location.